Pre-Serum Extract of Various Lime Mixed Rhizomes and Honey as A Functional Drink for Stamina for The Elderly - Ketut Wiradnyani; I made Yoga Parwata (Postgraduate, University of Mataram, 2024)
Sinom is a functional drink made from turmeric and young tamarind leaves. In its development, it has gone through in vitro and in vivo tests. In its development, Sinom underwent a change in formula after mixing lime and honey. Then it underwent a change in formulation as a serum in which the turmeric ingredient was replaced with various rhizomes, such as white turmeric rhizome, temu black, meet jokes and meetups black. This research aims to determine the macro compound content and the level of preference for the sinom pre-serum functional drink, a mixture of lime and honey from various rhizomes. This research uses an experimental method with a completely randomized design, determining proximate tests using treatment; S1R1 (Tumeric Rhizome mixed with lime and honey), S2R2 (White Turmeric Rhizome mixed with lime and honey), S3R3 (Rhizome of Temu Ireng mixed with lime and honey), S4R4 (Rhizome of Temu Lawak mixed with lime and honey), SxRx (Rhizome turmeric, white turmeric, temu black, meet buffoonery) a mixture of lime and honey. Proximate testing and organoleptic preference levels were carried out.The proximate test results are; S1R1; water content (70.111%), ash content (0.713%), protein content (0.758%), pH (3.995), S2R2 (white turmeric): water content (72.355%), ash content (0.831%), protein content (0.879 %), pH(3.836); S3R3: water content (75.788%), ash content (0.605%), protein content (0.766%), pH (3.728); S4R4: water content (75.975%), ash content (0.755%), Protein content 0.884%), pH (3.826); SxRx : water content (76.617%), ash content (0.777%), protein content (0.885%), pH (3.975). Organoleptic Test Results: SxRx's most preferred taste (4.03%), SxRx's aroma (3.96%), S4R4's color (4.00%) and S2R2's texture (3.36%). The conclusion obtained from this research was that the highest average water content was in the sinom treatment using turmeric rhizomes, white turmeric, curcuma ireng and curcuma (76.617%); Ash content in sinom using white turmeric (0.831%), the highest protein content in mixed sinom using various rhizomes (0.885%), the highest pH was found in sinom using turmeric rhizomes (3.995).